Urban Land Economics and Public Policy - Balchin, Paul N. author. aut Link
XV, 344 p.
Keywords: As a reflection of the change in the UK's economic strategy in recent years, this revised edition considers public policy in greater depth than previously with the inclusion of a chapter on welfare economics, analysis of trends in development and location and the effects of market changes.